2006
DOI: 10.1007/s00384-006-0121-x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological analysis and endoanal ultrasonography for diagnosis of anal fistula in acute anorectal sepsis

Abstract: Acute anorectal sepsis due to colonization of "gut-derived" microorganisms rather than "skin-derived" organisms is more likely to be associated with anal fistula. When the microbiological analysis yields gut-derived bacteria, but no fistula has been found in the initial drainage operation, repeat examinations during a period of quiescence, including careful digital assessment and meticulous endosonography, are warranted to identify a potentially missed anal fistula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 11 publications
1
43
0
5
Order By: Relevance
“…In the present study, we found that the incidence of GIT and skin-derived microorganisms was 78% and 22%, respectively and it is similar to other studies. 11,12 The result of this study supported that GIT-derived organisms, such as E. coli, Bacteriodes spp. and Enterococcus spp., and skin-derived organisms such as coagulasenegative Staphylococci and S. aureus were significantly more frequent.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In the present study, we found that the incidence of GIT and skin-derived microorganisms was 78% and 22%, respectively and it is similar to other studies. 11,12 The result of this study supported that GIT-derived organisms, such as E. coli, Bacteriodes spp. and Enterococcus spp., and skin-derived organisms such as coagulasenegative Staphylococci and S. aureus were significantly more frequent.…”
Section: Discussionsupporting
confidence: 68%
“…The mean age of patients was 39.8 and it was similar to other studies. 5,12,14 Most aerobic and anaerobic organisms isolated from the PAes are of GIT and skin flora origin. 5 The isolation of anaerobic bacteria together with aerobic organism at that site is not surprising, since anaerobes are the predominant organisms in GIT where they outnumber aerobes in a ratio of 1,000:1.…”
Section: Discussionmentioning
confidence: 99%
“…Dieses wird auch von aktuellen Publikationen bestä-tigt [22]. Mehrere ältere Arbeiten ver-weisen auf eine höhere Fistelinzidenz bei Nachweis von Darmkeimen [37,117]. Nicholls et al [76] konnten keinen Zusammenhang zwischen dem Nachweis von Bacteroides spec.…”
Section: äTiologie Und Klassifikationunclassified
“…It is directed downwards and backwards. It is surrounded by inner involuntary and outer voluntary sphincters which keep the lumen closed in the form of an anteroposterior slit [2].…”
Section: Normal Anatomy Of the Anal Canal In Axial Planementioning
confidence: 99%